From Lab to Table: Islamic Jurisprudential Analysis of Cultured Meat Production - Nor Farhana Humairah Nordin; Nur Aufa Amilee Addie Irman; Intisya’ Adnin Zulaikha Mohd Shuhaidi; Batrisya Nur Mohd Kafli; Mohd Harifadilah Rosidi (RSIS International, 2025)
Indexed Publication (Tier 2)